Are African Universities Centres of Excellence? The Consumer Perspective of Ugandan Universities. - Kasenene, E. S. (African Journals Online (AJOL), 2009)
Universities the world over, strive to be centres of excellence, notwithstanding the differences in the scope of their educational fields. Universities in Africa, particularly those in Uganda, are not exceptional. However, whether those in Uganda have attained this end or not, is still questionable. Accordingly, this article employs a consumer perspective of educational excellence to establish the extent to which Ugandan universities have achieved this goal. The article is based on perceptions of 355 students selected from three private and two public universities in Uganda. The perceptions are analysed using ANOVA and factor analysis methods of SPSS. Results show that from the consumer perspective, universities in Uganda are at significantly different levels of excellence. While some are promising to fully become centres of excellence, others are still far below students’ expectations as far delivering educational services as concerned; yet the position of other universities is still uncertain, particularly in terms of information services needed by students to research, enrich knowledge, and develop their talents and skills as desired; offering educational programmes or courses that help students to develop skills needed to be competent at work after training; and professional approach to the delivery of the services Put in place all information services needed by students to research, enrich knowledge, and develop their talents and skills as desired. The article is therefore concluded by noting that Ugandan universities need to strengthen the reliability, assurance and responsive of their educational services to the extent to which their enrolled students perceive them as centres of excellence. Accordingly, it is recommended that these universities should put offer educational programmes and information services needed by enrolled students and deliver them in a way that is professionally desired by students